Correlation between Body Mass Index and Cartilage Oligomeric Matrix Protein Levels in Woman with Postmenopausal Symptomatic Osteoarthritis - IGN Wien Aryana (Journal of Global Pharma Technology, 2016)
Background: Measurement of serum cartilage oligomeric matrix protein (sCOMP) concentration is expected to be new approach for osteoarthritis early detection. Osteoarthritis has been linked to obesity as its risk factor. This study aimed to determine relationship between BMI and sCOMP in woman with symptomatic osteoarthritis. Methods: : A cross-sectional study was done using consecutive sampling. The study population comprised of female patients age 50-70 y.o who had menopause since last 1 year and symptomatic knee arthritis. Osteoarthiris were comfirmed by genu imaging. sCOMP concentration were determined in Clinical Phatology Laboratorium of Sanglah Hospital using ELISA technique. The body mass index was calculated using the standarized formula. Correlation test was used to determine the correlation between body mass indexes with sCOMP level. Results: From total of 68 participants, the mean age was 73.66 (SD 9.356), the mean BMI was 21.97 (SD 4.66), and the mean sCOMP concentration was 7.935 (SD 10.11). Significant correlations (p <0.01) occured for this sample. However, Spearman’s rho was quite low (r = -0.382), indicating only weak correlations. A higher BMI was associated with lower sCOMP concentration. Conclusion: The results prove the relationship between BMI and sCOMP concentration. Further research is needed to reveal causality between both variables.Keywords: Osteoarthitis, Women, BMI, sCOMP concentration.